2022
DOI: 10.3390/cancers14081862
|View full text |Cite
|
Sign up to set email alerts
|

The Entanglement between Mitochondrial DNA and Tumor Metastasis

Abstract: Mitochondrial DNA, the genetic material in mitochondria, encodes essential oxidative phosphorylation proteins and plays an important role in mitochondrial respiration and energy transfer. With the development of genome sequencing and the emergence of novel in vivo modeling techniques, the role of mtDNA in cancer biology is gaining more attention. Abnormalities of mtDNA result in not only mitochondrial dysfunction of the the cancer cells and malignant behaviors, but regulation of the tumor microenvironment, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 130 publications
(154 reference statements)
0
2
0
Order By: Relevance
“…Juntermanns et al reported that high-dose of radiation ( 20Gy) can damage the tumor's vascular obviously and induce the hypoxic condition of the tumor microenvironment [48], and then hypoxia inducible factor 1 (HIF-1α) incurred in the hypoxic condition can activate migratory and angiogenic genes such as VEGF, MMP-2, and Vimentin [49][50][51]. Other studies reported that radiation induces tumor metastasis through cytokine/chemokine signaling [52] or mitochondrial damage [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…Juntermanns et al reported that high-dose of radiation ( 20Gy) can damage the tumor's vascular obviously and induce the hypoxic condition of the tumor microenvironment [48], and then hypoxia inducible factor 1 (HIF-1α) incurred in the hypoxic condition can activate migratory and angiogenic genes such as VEGF, MMP-2, and Vimentin [49][50][51]. Other studies reported that radiation induces tumor metastasis through cytokine/chemokine signaling [52] or mitochondrial damage [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…The morphology, localization, and functions of mitochondria in CSCs differ from normal cells, normal stem cells, and cancer cells. [163][164][165][166] CSCs express fewer mitochondrial DNA copies (mtDNA) and low levels of mitochondrial transcription factor A (TFAM) in contrast to normal cells which express many copies of mtDNA and TFAM. 163,165,166 Notably, during the process of fibroblast remodeling into iPSCs, a significant reduction in the number of mitochondria takes place, accompanied by decreased mtDNA, mitochondrial mass, and low ROS levels in the stem cells.…”
Section: Mitochondrion -A Key Organelle In Cancer Stem Cellsmentioning
confidence: 99%
“…EMT has also been associated with mitochondrial dysfunction, which regulates the tumor microenvironment, leading to more aggressive tumors. Wu and colleagues reviewed the recent progress in the regulation of cancer metastasis by mitochondrial DNA, showing its impact on different aspects, including resistance to anoikis, promotion of angiogenesis, cancer cell survival in the circulatory system, and colonization [10]. Moreover, mitochondrial dysfunction leads to metabolic reprogramming and proteome rewiring.…”
mentioning
confidence: 99%